2004
DOI: 10.1128/jcm.42.11.4974-4976.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal versus Oropharyngeal Sampling for Detection of Pneumococcal Carriage in Adults

Abstract: Several studies have shown that nasopharyngeal sampling is more sensitive than oropharyngeal sampling for the detection of pneumococcal carriage in children. The data for adults are limited and conflicting. This study was part of a larger study of pneumococcal carriage on the Navajo and White Mountain Apache Reservation following a clinical trial of a seven-valent pneumococcal conjugate vaccine. Persons aged 18 years and older living in households with children enrolled in the vaccine trial were eligible. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
61
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 15 publications
11
61
0
1
Order By: Relevance
“…The second issue is the use of the rigid swab applicator to sample the nasopharynx, as was done in some earlier studies (1, 6), and not the flexible swab applicator, as was done in others (4,9,12). At the preliminary stage of this study the investigators tested both types of applicators for nasopharyngeal sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second issue is the use of the rigid swab applicator to sample the nasopharynx, as was done in some earlier studies (1, 6), and not the flexible swab applicator, as was done in others (4,9,12). At the preliminary stage of this study the investigators tested both types of applicators for nasopharyngeal sampling.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivities of these two methods for identification of colonization by PRP in adults were compared in several earlier studies, particularly regarding S. pneumoniae, but the results were not consistent (1,2,4,6,9,12). The nasopharyngeal wash technique, which is commonly used to isolate viruses in children, has not gained popularity as a method to test for PRP colonization in adults.…”
mentioning
confidence: 98%
“…Although multiple strains can colonize simultaneously (4,5,(7)(8)(9)(10), most surveillance studies characterize only single colonies-but how valid is this information (12)? Nasopharyngeal swabs capture more pneumococci than throat swabs (1,6,14), but throat swabs can uncover different phenotypes (13,16). Our carriage studies (submitted for publication) characterizing multiple colonies from nose and throat samples revealed that Tanzanian children were colonized by a mean of three different serogroups or -types (SGT) and two different antibiograms for penicillin and cotrimoxazole.…”
mentioning
confidence: 90%
“…21 A predicted carriage rate of 20% in 800 participating older children and adults would enable the determination of true carriage to within ±2.8% (95% confidence). 9 Participant recruitment Participants were selected from 20 GP practices within the Wessex Primary Care Research Network (PCRN) South West (East hub) area, in Southern England. GP practices were chosen to reflect a mix of urban/rural locations, practice sizes and area deprivation levels.…”
Section: Sample Sizementioning
confidence: 99%
“…Methods for assessing carriage have included swabbing, nose blowing and nasopharyngeal aspiration. [5][6][7][8][9][10][11][12] However, no single study has evaluated the use of different swabbing methods using a large population-based sample. Streptococcus pneumoniae remains the…”
Section: Introductionmentioning
confidence: 99%